Model predictive control for systems with stochastic multiplicative uncertainty and probabilistic constraints - Cannon, M; Kouvaritakis, B; Wu, X (2009)
Robust predictive control handles constrained systems that are subject to stochastic uncertainty but propagating the effects of uncertainty over a prediction horizon can be computationally expensive and conservative. This paper overcomes these issues through an augmented autonomous prediction formulation, and provides a method of handling probabilistic constraints and ensuring closed loop stability through the use of an extension of the concept of invariance, namely invariance with probability p. © 2008 Elsevier Ltd. All rights reserved.